(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2023)
Beyond insulation, consideration of the effect of the thermal properties of the ceiling materials on the airflow and heat distribution within the attic are important in building design. This study examines this impact for asbestos, particle board, plywood and PVC ceilings under a complex-shaped pitched roof heated from below using ANSYS Fluent V(18) package. Results showed multicellular flow patterns for all the materials. Air speed within the attic increases with the use of asbestos, PVC, particle board and plywood. Generally, pressure is lowest at the upper vertex and highest near the bottom corners. The pressure maximum value is lowest in the particle board ceiling and highest in the asbestos ceiling. Therefore, on the flowfield, asbestos makes the best choice and plywood the least. In terms of thermal performance, particle board ceiling is best recommended, then the PVC, the asbestos and plywood. In a sample building, the rate of heat loss into the attic through a plywood ceiling is found to be about 7% higher than when particle board is used. This has huge building energy-saving and air-conditioning implications.